Association of Trauma Alert Response Charges With Volume and Hospital Ownership Type in Florida - Jessica L. Ryan; Etienne E. Pracht; Barbara Langland-Orban (SAGE Publishing, 2018)
Objective: The purpose was to analyze the association of trauma volume and hospital trauma center (TC) ownership type with trauma alert (TA) response charges, which are billed for activation of the trauma team to the emergency department (ED). Methods: All Florida ED and inpatients who were billed a TA charge from 2012 to 2014 were included (62 974 observations). Multiple linear regression, controlling for patient and hospital factors, was used to identify associations between TA charges and trauma volume and hospital ownership type. Severity elasticity of trauma response charges was calculated by ownership type. Results: Trauma volume had a significant, inverse relationship with TA charges. For-profit (FP) hospitals had significantly higher TA charges and government-owned hospitals had significantly lower TA charges relative to private not-for-profits. For-profit trauma response charges were inelastic to severity, that is, charges did not change with changes in severity. Conclusion: Higher TA charges were associated with lower patient volumes, as well as at FP TCs. Further, only FP TCs used alert charges that were not associated with injury severity. Adding new TCs that reduce volume at existing TCs is expected to increase TA charges, especially if they are FP TCs.